Pengaruh festivalscape terhadap pengalaman emosi dan otentik, kepuasan pengunjung, dan revisit intention - Sudiro, Dedy Aditya; Suroso, Agus; Novandari, Weni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2017)
Background: Indonesia is a country that has huge potential in tourism supported by its various natural beauties and also culture. One of the ways to take the advantage is by creating a cultural festival which can promote the city and also conserve the cultural heritage. Purpose: This study examines the influence of festivalscape (program content, staff, facility, food, and beverage) to emotional and authenticity experience, visitor satisfaction, and revisit intention in Festival Jenang Solo 2017. Findings: Results of PLS (Partial Least Square) analysis, outer model, inner model, and hypothesis testing using t-test are (1) festivalscape (program content, staff, food, and beverage) has positive and significant effect on emotional experience, (2) festivalscape (program content, food, and beverage) has positive and significant effect on authenticity experience, (3) emotional experience has positive and significant effect on visitor satisfaction, (4) authenticity experience has positive and significant effect on visitor satisfaction, and (5) visitor satisfaction has positive and significant effect on visitor’s revisit intention. Implications: The implications from the explanation above are that the Festival Jenang Solo should pay more attention and improve the quality of the existing festivalscape as it can provide an emotional and authenticity experience. By increasing the emotional and authenticity experience, it will automatically increase the visitor’s satisfaction. The visitors who are satisfied to a festival will have intention to revisit in the future. Keywords: festivalscape, emotional experience, authenticity experience, visitor satisfaction, revisit intention.